EFFECT OF STORE IMAGE ON LOYALTY STORE THROUGH STORE SATISFACTION IN ISLAMIC SWALAYAN STORES - Muhammad Arief; Dwi Hendro Widayatmoko (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2018)
Purchasing a product or shopping in an Islamic supermarket or store is something that is unique with many factors which will affect the consumer. One of the factor that influences consumer when choosing to shop in a certain store is the image that arises and attaches to that store. A good image of the store will affect the consumer to keep shopping and become loyal to the store. Consumer satisfaction when shopping in a store is also a factor that influences the loyalty of the consumer to that particular store. Furthermore, a good image plays an important on making the consumer satisfied, and together will influence the consumer to become loyal to that store.